2020
DOI: 10.17582/journal.aavs/2020/8.5.536.542
|View full text |Cite
|
Sign up to set email alerts
|

Growth Performance, Morphological and Chemical Characteristics of Red Tilapia Fed Diets Supplemented with Dunaliella salina

Abstract: The aims of the present study were to investigate growth performances, morphological and chemical body characteristics, blood profiles of Red Tilapia upon dietary Dunaliella salina (D. salina) supplementation. Control and D. salina diets were formulated isonitrogenous and isoenergetic (339.99±0.02 g/kg & 4.5 ± 0.0028 Kcal/g, respectively) and fed during the study. The formulated diets were control diet and D. salina diets supplemented with 33.0, 66.0 and 100% and fed thrice a day to fish (14.37±0.15 g g) for f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“… Abdelwahab et al (2020) indicated that the substitution of fish meal with a low level of D. salina (33.0%) produced similar findings as the control diet with respect to BWG and FCR. Fernandes et al (2020) reported that D. salina has favorable bioactive concentrations of constituents, which may be used in poultry feed.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“… Abdelwahab et al (2020) indicated that the substitution of fish meal with a low level of D. salina (33.0%) produced similar findings as the control diet with respect to BWG and FCR. Fernandes et al (2020) reported that D. salina has favorable bioactive concentrations of constituents, which may be used in poultry feed.…”
Section: Discussionmentioning
confidence: 66%
“…Recent interest has grown in the use of D. salina as a novel feed supplement for nutritional purposes ( Mohammed, 2018 ). D. salina provides many health benefits to animals due to its high β -carotene content, which can safeguard against central nervous system O 2 toxicity ( Bitterman et al, 1994 ) and gut inflammation through antioxidant and immunomodulatory properties ( Abdelwahab et al, 2020 ). A broiler chick's diet supplemented with D. salina and Spirulina is predicted to extend favorable impacts on birds.…”
Section: Introductionmentioning
confidence: 99%
“…The color of fish flesh minces of control and biofloc groups were determined using Hunter (Almadani, 2017;Abdelwahab et al, 2020). Mince color examination of L, a , and b values are used to determine color of fish flesh minces of control and biofloc groups.…”
Section: Color Of Fish Flesh Minces Measurementmentioning
confidence: 99%
“…The demand for these products has increased steadily, along with the increase in the demand for feed. It is known that protein is one of the main components of feed for aquatic organisms such as fish and crustaceans (Abdelwahab et al, 2020). Fish feed is considered more than half of the costs of the fish farming project.…”
Section: Introductionmentioning
confidence: 99%
“…Dietary microalgae inclusion in small or large amounts to mammalian and fish species are considered one of the most important feed supplements for improving nutritional values and productive performances throughout the world (Abdelwahab et al, 2020;2023). They gained prominence and limelight continuous interest because of their crucial roles for mammalian and fish species (Mohammed 2018(Mohammed , 2022Ali et al, 2021;Al-Mafurji et al, 2022;Molina-Roque et al, 2022).…”
mentioning
confidence: 99%